EFFICACY OF FASCIA ILIACA BLOCK FOR ACUTE PAIN MANAGEMENT IN PATIENTS WITH HIP FRACTURES. A PROSPECTIVE COHORT STUDY - RAFIQ , SU; AHMAD , T; GHAZNI , MA; JAMAL , S; NOORDIN, S; SULAIMAN , MA (Biological and Clinical Sciences Research Journal, 2024)
The fascia iliaca block is a compartment field block that effectively treats pain from hip fractures and hip surgeries. Fascia iliaca block reduces preoperative and postoperative pain scores, postoperative opioid consumption, and the occurrence of opioid-related adverse events. Objective: To assess the efficacy of fascia iliaca block for acute pain management in patients with hip fractures. Methods: Thirty-three patients of both genders were included. Fascia iliaca Block was applied using a landmark-based technique. The Numeric Rating Score was measured. The normality of data was checked, and the Median (IQR) was reported due to non-normal distribution. Frequencies and percentages were calculated for qualitative variables. The Chi-square/fisher exact test was applied to determine the association between qualitative variables, while odds were calculated by binary logistic regression. Friedman and Wilcoxon Signed Ranks Test made comparisons for quantitative variables. Results: [PAIN SCORE pre+post block. Resue analgesia %]. Males are more likely than females to need rescue analgesia (OR=1.161, p=0.840). Compared to patients over 65, those under 65 are less likely to require rescue analgesia (OR=0.900, p=0.900). There was a significant difference throughout the periods, with the median VAS score before FIB, at 15 minutes, at 1 hour, at 6 hours, and at 12 hours being 9 (IQR:8-10), 5 (IQR:3-6), 2 (IQR:1-3), 2 (IQR:1.5-4), and 5 (IQR;4-6), respectively. Conclusion: The fascia iliaca block for hip fractures is an effective pain management method. It also provides postoperative short-term analgesic effects both at rest and with movement.